Association of objectively measured physical activity and sedentary time with health-related quality of life in women with fibromyalgia: The al-Ándalus project - Blanca Gavilán-Carrera; Víctor Segura-Jiménez; Fernando Estévez-López; Inmaculada C Álvarez-Gallardo; Alberto Soriano-Maldonado; Milkana Borges-Cosic; Manuel Herrador-Colmenero; Pedro Acosta-Manzano; Manuel Delgado-Fernández (Elsevier, 2019)
Purpose: To examine the association of physical activity (PA) intensity levels and sedentary time with health-related quality of life (HRQoL) in women with fibromyalgia and whether patients meeting the current PA guidelines present better HRQoL. Methods: This cross-sectional study included 407 women with fibromyalgia aged 51.4 ± 7.6 years. The time spent (min/day) in different PA intensity levels (light, moderate, and moderate-to-vigorous physical activity (MVPA) and sedentary time were measured with triaxial accelerometry. The proportion of women meeting the American PA recommendations (≥150 min/week of MVPA in bouts ≥10 min) was also calculated. HRQoL domains (physical function, physical role, bodily pain, general health, vitality, social functioning, emotional role, and mental health), as well as physical and mental components, were assessed using the 36-item Short-Form Health Survey. Results: All PA intensity levels were positively correlated with different HRQoL dimensions (rpartial between 0.10 and 0.23, all p < 0.05). MVPA was independently associated with social functioning (p < 0.05). Sedentary time was independently associated with physical function, physical role, bodily pain, vitality, social functioning, and both the physical and mental component summary score (all p < 0.05). Patients meeting the PA recommendations presented better scores for bodily pain (mean = 24.2 (95%CI: 21.3-27.2) vs. mean = 20.4 (95%CI: 18.9-21.9), p = 0.023) and better scores for social functioning (mean = 48.7 (95%CI: 43.9-44.8) vs. mean = 42.3 (95%CI: 39.8-44.8), p = 0.024). Conclusion: MVPA (positively) and sedentary time (negatively) are independently associated with HRQoL in women with fibromyalgia. Meeting the current PA recommendations is significantly associated with better scores for bodily pain and social functioning. These results highlight the importance of being physically active and avoiding sedentary behaviors in this population. Keywords: Accelerometry, GT3X+, Mental health, Physical health